Transformational Leadership and Workplace Spirituality on Employee Performance Mediated by Organizational Commitment - Ni Kadek Nonik Rasminingsih; I Made Aditya Wardana; Putu Ari Pertiwi Sanjiwani (AIBPM Publisher, 2022)
Nowadays, competition in business industries is very tight that makes Human Resource is the most valuable aspect for a firm to stay as well as to keep survive. 160 employess of LPD that located in Kecamatan Denpasar Timur were used as sample. Purposive sampling method and PLS (Partial Least Square) analysis technique used in this research. The result showing that transformational leadership and workplace spirituality positive- significantly affect employee’s performances. Transformational leadership also workplace spirituality leadership positive-significantly affect organizational commitments Organizational commitments positively and significantly effect on employees’ performances. Organizational commitments proven to strengthen and mediates transformational leadership to employee’s performance. Organizational commitment proven to strengthen and mediates workplace spirituality on employee’s performance. Purposes of the research show that this research can be utilized as reference to a firm in order to focus on the antecede that improves employees’ performances Keywords: Transformational leaderships, Workplaces spirituality, Organizational commitments, Employees performances